Halal Marketing Elements as Determinants of Consumer Product Purchase Decisions - Heryanto, Heryanto; Firdaus, Firdaus; Syafrizal, Syafrizal (Indonesia Journal of Halal, 2022)
This research aimed to analyze the effect of halal marketing elements on consumer choice using positivist paradigm and quantitative methods. The population consisted of 398561 residents working in Padang City, following the August 2019 National Labor Force Survey. The Slovin's formula was used to obtain a sample size of 400 respondents. Moreover, purposive sampling technique was used to obtain data, which was then analyzed using path analysis. The main focus was on the elements of halal marketing that contribute to consumer product purchase decisions. The results showed that consumer option is determined by the core elements of halal marketing, including halal positioning, differentiation, and branding. Furthermore, halal positioning and differentiation significantly affect branding and consumer choice. Halal consumer choice is affected by positioning and differentiation through branding. Halal positioning affects the implementation of high and low halal branding by 52%. Halal differentiation affects the high and low halal branding by 21%. Halal consumer choice is affected by positioning, differentiation, and branding at 28%, 35%, and 30%, respectively. These results indicated a low indirect effect of branding. Implementing high and low halal consumer choice is affected by positioning and differentiation through branding at 18% and 7%, respectively.